he real Thalang battlefield of 1785 take place at Tarruah bay and Tarruah town. Tarruah town is the real Thalang town in the era of Thao Thep Kasattri. - Manosoonton, Ekapol (RUSAMILAE JOURNAL, 2022)
The seminars on Thalang history in Phuket concluded that Thalang battlefield of 1785 take place at "Koke Pamar or Thung Thalang Chanasuek, Ban Takian" and Ban Takhian town is Thalang town in the era of Thao Thep Krasattri, because Jom Rang, Governor of Ban Takian town, a father of Thao Thep Krasattri and Thao Thep Krasattri live in Ban Takian town. During 2018-2022, the primary evidences are discovered such as a map of Thalang Island of French (1745), and a map of Thalang Island of the Dutch East India Company (VOC) (1753) and a map of Thalang Island by Captain Forrest of the British East India Company (1784). And the reports of Captain Light and Captain James Scott and Captain John Bemele to John McPherson Esq. Governor General President at Fort William, Straits Settlements Consultations, Headquarters. These primary evidences reveal the fact that 1) The real Thalang Battlefield of 1785 take place at Tarruah bay and Tarruah town. 2) Junk Ceylon town or Jukseilon town is Tarruah town or the real Thalang town in the era of Praya Phimon and Thao Thep Kasattri, not Ban Takian town. 3) "The Thalang battlefield of 1785 take place at Koke Pamar or Thung Thalang Chanasuek, Ban Takian" is a fake story and has never actually happened in the history of Thalang".